Review: Utility of mass spectrometry in rare disease research and diagnosis - Teresa Zhao; Daniella H. Hock; James Pitt; David R. Thorburn; David A. Stroud; John Christodoulou (npj Genomic Medicine)
Abstract Individuals affected by a rare disease often experience a long and arduous diagnostic odyssey. Delivery of genetic answers in a timely manner is critical to affected individuals and their families. Multi-omics, a term which usually encompasses genomics, transcriptomics, proteomics, metabolomics and lipidomics, has gained increasing popularity in rare disease research and diagnosis over the past decade. Mass spectrometry (MS) is a technique allowing the study of proteins, metabolites and lipids and their fragments at scale, enabling researchers to effectively determine the presence and abundance of thousands of molecules in a single test, accurately quantify their specific levels, identify potential therapeutic biomarkers, detect differentially expressed proteins in patients with rare diseases, and monitor disease progression and treatment response. In this review, we focus on mass spectrometry (MS)-based omics and survey the literature describing the utility of different MS-based omics and how they have transformed rare disease research and diagnosis.